Evaluation of metal additive manufacturing for high-field modular-stellarator radial plates and conductors. (March 2022) - Queral, V.; Rincón, E.; Cabrera, S.; Lumsdaine, A.
Highlights: Metal additive manufacturing tested for high field stellarator radial plates. 3D-printing of stellarator windings performed in copper and aluminium. Stainless Steel 316 proved accurate and strong by Selective Laser Melting SLM. Conductor windings produced by Electron Beam Melting (EBM) of pure copper. Variable cross-section windings satisfactorily printed with Al and Cu. Abstract: The utilization of metal additively manufactured radial plates and conductors for high-field modular-stellarator coils is assessed, particularly, for resistive coils having turns of variable cross-section (additively manufactured aluminium or copper turns). This concept of radial plates might also be applicable to superconducting wire and resistive conductors of constant cross-section. Modular coils and their winding packs for (high-field) stellarators require high precision, durability under high internal Lorentz forces and thermal stresses, stiffness and strength, in rather contorted components. Radial plates have been utilized in tokamaks (i.e. ITER) and are proposed for tokamak and stellarator reactors (i.e. FFHR), particularly when the high Lorentz forces may compromise the mechanical integrity of the insulation and winding pack. Radial plates for tokamaks have been produced by milling steel plate, and welding different segments if the size requires it. However, the contorted shape of stellarator modular coils makes the manufacturing of radial plates more challenging. This suggests the possible use of additive manufacturing, which is particularly appropriate for short series of geometrically complex parts. In relation to those matters, this work investigates whether metal additive manufacturing of contorted radial plates and metallic conductor turns (windings, to be introduced in the radial plates) of variable cross-section and proper insulation, may be satisfactory for small or middle size high-field stellarators. The emphasis is placed on the accuracy, mechanical properties and cost of those parts. The feasibility, advantages and weakness of the additive manufacturing process and the assembling procedure are tested and studied. With the present commercial metal 3D printers, metal additively manufactured radial plates will require final milling to achieve enough accuracy. Coil casings appear feasible without final milling, and windings of variable cross-section, produced from brazing modified flexible copper wire, are promising.